2010
DOI: 10.1039/b917852j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of substituents on the excited-state dynamics of the modified DNA bases 2,4-diaminopyrimidine and 2,6-diaminopurine

Abstract: To explore the excited state dynamics of pyrimidine derivatives, we performed a combined experimental and theoretical study. We present resonant two-photon ionization (R2PI) and IR-UV double resonance spectra of 2,4-diaminopyrimidine and 2,6-diaminopurine seeded in a supersonic jet by laser desorption. For 2,4-diaminopyrimidine (S(0)-->S(1) 34,459 cm(-1)), we observed only the diamino tautomer with an excited state lifetime bracketed between experimental limits of 10 ps and 1 ns. For 2,6-diaminopurine, we obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
39
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 99 publications
13
39
3
Order By: Relevance
“…The spectrum is characterized by a single broad band with origin at 4.46 eV and maximum at 5.10 eV. In our previous study on 2,4-DAPy and related compounds we have shown that these values obtained using the CC2/SVP method [23] are uniformly shifted by 0.31 eV to lower energy with respect to present CASSCF results. The vertical excitation energies and oscillator strengths of the 2 1 A 1 (pp * ) and 3 1 A 1 (np * ) states calculated at the CASSCF level are indicated in the graph.…”
Section: Absorption Spectra Of 24-dapymentioning
confidence: 91%
See 2 more Smart Citations
“…The spectrum is characterized by a single broad band with origin at 4.46 eV and maximum at 5.10 eV. In our previous study on 2,4-DAPy and related compounds we have shown that these values obtained using the CC2/SVP method [23] are uniformly shifted by 0.31 eV to lower energy with respect to present CASSCF results. The vertical excitation energies and oscillator strengths of the 2 1 A 1 (pp * ) and 3 1 A 1 (np * ) states calculated at the CASSCF level are indicated in the graph.…”
Section: Absorption Spectra Of 24-dapymentioning
confidence: 91%
“…Calculated linear interpolation curves of 2,4-DAPy between the S 1 minima towards various MXS reported in our previous study [23] show that the additional NH 2 group causes a sizeable barrier of about 1 eV on the reaction paths towards the 1 S 2 structure thereby immobilizing the MXS located at the C2 atom. There are however still other paths connecting the S1min_C6 with other MXSs ( 1 S 6 and B 1,4 and 3 H 4 ) with negligible barriers allowing for a fast relaxation process.…”
Section: Potential Energy Surfaces Of 4-apy and 24-dapymentioning
confidence: 97%
See 1 more Smart Citation
“…[36,37] represents Ade in several interesting aspects (vertical excitations, MXS structures and reaction paths) very well. Moreover, 4-APy is also of interest in connection with investigations on the photophysics of diaminopyrimidine [38,39], which forms an unnatural base pair with xanthine [40]. Water was chosen as solvent because of its outstanding importance for biological systems.…”
Section: Introductionmentioning
confidence: 99%
“…Will it be long-lived? The answer can be given from previous experience with the dynamics of 6-APy (40) and recent static (41) and photodynamical (42) calculations for 2,6-DAPy, which show that either keeping or not the blocking C 2 substitution on the pyrimidine ring, the removal of the imidazole ring will allow fast deactivation by puckering at the C 4 position.…”
Section: Characterization Of Conical Intersectionsmentioning
confidence: 99%